ANALYSIS OF THE DIVERSITY OF UNDERSTORY SPECIES AT THE GREENHOUSE DEPARTMENT OF BIOLOGY, UIN ALAUDDIN MAKASSAR - Rustam, Aswar; Hamzah, Pratiwi (JURNAL BIOSAINS, 2024)
Undergrowth is one of the constituents of a forest vegetation ecosystem. Over time, the condition of the land that has experienced succession will be overgrown by pioneer species and become understory. This research is to determine the distribution of understory species at the post-land clearing location at the greenhouse construction site, Department of Biology, UIN Alauddin Makassar. The variables of this research are diversity, evenness, dominance, and community similarity of understory plants that live in that location. Based on observations, the species distribution at the study site reached 35 species in 3 observation points. This condition indicates that the understory species in the research area are abundant and dominated by L. Nummularia, S. obtusifolia, and C. dactylon. The community similarity index shows a figure of 12%, which means the categories are not the same. The species diversity index shows that the three observation plots are moderate. Regarding the evenness, only S. nodiflora had a moderate evenness (0.6 â‰¤ e â‰¤ 0.4). Meanwhile, species with low evenness (e < 0.4) were C. dactylon, S. tora, and S. obtusifolia.